The Na+/H+ Exchanger NHX1 Controls H+ Accumulation in the Vacuole to Influence Sepal Color in Hydrangea macrophylla - Gaitian Zhang; Suxia Yuan; Hui Qi; Zhiyun Chu; Chun Liu (International Journal of Plant Biology, 2023)
Hydrangea macrophylla is popular for its unique physiological characteristics and changeable colors. Previous studies have shown that the pH of the vacuoles of the sepal cells of hydrangea affects the color of the sepals. Located on the vacuolar membrane, NHX1 is an important H+ proton pump that drives the exchange of metal ions. This proton pump affects the physiological environment by controlling the accumulation of H+ in the vacuole. In hydrangea, the HmNHX1 gene has an open reading frame of 1626 bp and encodes a total of 541 amino acids. Bioinformatic analysis showed that HmNHX1, which encodes a Na+/H+ exchanger, is located on the vacuolar membrane. Tissue-specific expression analysis showed that the expression of this gene in the treatment group was higher than that in the control group. The ion flux in the vacuoles of colored hydrangea in the treatment group and the control group were measured, and the results showed that HmNHX1 was indeed a Na+/H+ exchanger. When the results of the HmNHX1 expression analysis and ion flux measurements are combined, it can be seen that HmNHX1 regulates the accumulation of H+ in the vacuole, ultimately affecting the color of the plant.